Membangun Kesadaran Lingkungan dan Komunitas Berkelanjutan melalui Pembelajaran PAI - Liya Qurrotu A'yun; Lina Marlina; Widya Agustina (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Environmental awareness and sustainable community development are global issues that require the active participation of various sectors, including education. Islamic Religious Education (PAI), as an integral part of the education system, holds significant potential for shaping attitudes, behaviors, and values ​​of environmental concern. This literature review aims to analyze the contribution of PAI to building ecological awareness and sustainable communities through the integration of Islamic values, learning strategies, and character building. The study was conducted by reviewing various national and international studies that discuss the relationship between religious values, education, ecological behavior, and community development. The results of the review indicate that Islamic concepts such as khalifah (vicegerent), amanah (trust), mizan (property), ihsan (good deeds), and the prohibition of isrāf (unlawful acts) serve as a strong environmental ethical framework for PAI learning. The integration of environmental materials into the PAI curriculum can improve students' ecological literacy, foster pro-environmental behavior, and develop a collective awareness of maintaining the balance of nature. Furthermore, project-based learning models, community service (service learning), and spiritual practices have been shown to strengthen students' concrete actions in building sustainable communities. This study concludes that strengthening environmental education in Islamic Religious Education (PAI) not only increases knowledge but also fosters ecological character and community collaboration. Synergy between schools, families, and communities is necessary to implement Islamic environmental values ​​in daily life.